Correction: Olteanu et al. Interleukin-4 Gene Polymorphisms in Romanian Patients with Inflammatory Bowel Diseases: Association with Disease Risk and Clinical Features. Diagnostics 2023, 13, 1465 - Andrei Ovidiu Olteanu; Elena Mirela Ionescu; Cristian George Tieranu; Luis Ovidiu Popa; Silvia Ioana Andrei; Carmen Monica Preda; Monica Irina Dutescu; Mihai Bojinca; Ioana Tieranu; Olivia Mihaela Popa (Diagnostics)
The authors wish to correct the authorship of the original publication [...]